Efektifitas Penerapan Sistem Pengendalian Intern Pemerintah Dalam Meningkatkan Kualitas Laporan Keuangan (Studi Pada Pemerintah Kota Pematangsiantar - Silitonga, Hery Pandapotan; Gultom, Jenni; Sembiring, Lenny Dermawan (Universitas Nusantara PGRI Kediri, 2020)
This study aimed to determine the effectiveness of the implementation of the government internal control system to improve the quality of financial statements. The research design used was literature research that utilized a literature review as a reference. The data collection used the documentation and questionnaire methods by distributing questionnaires to the sample. The study was conducted from May 2020 to July 2020. The research population was the Regional Apparatus Organization of Pematangsiantar City. The flow of activities carried out in this study was carried out with an interactive cycle process. The reduced data were presented in the form of descriptions in accordance with the aspects of the study, which aimed to make it easier for researchers to interpret data and draw conclusions. Based on the results of the study that has been conducted, it is concluded that the effectiveness of the implementation of the government internal control system carried out by the Pematangsiantar City Government could improve the quality of the financial statements issued.